The success of the home industry-based coffee business (kaduwa) - Syauqi, Raihan -; Prajawati, Maretha Ika (Maliki Interdisciplinary Journal, 2026)
This study aims to analyze the success of the home industry-based coffee business KADUWA as part of MSMEs in Malang City. The research employs a qualitative method with a phenomenological approach through observation, interviews, and documentation. The findings reveal that KADUWA’s success is not solely determined by product quality but also by its simple yet strong branding that emphasizes local identity, a family-like atmosphere, and friendly interpersonal services. The “Koentjik Kewarasan” concept creates an emotional experience for customers, enhancing loyalty. In addition, human resource management, product innovation, and digital-based marketing strategies play crucial roles in sustaining the business. The study also highlights the importance of risk management and adaptability to market changes. Recommended strategies include improving facilities, diversifying products, optimizing digital branding, and enhancing human resource capacity. This research contributes to the development of literature on coffee-based MSMEs and provides practical insights for entrepreneurs in designing sustainable and competitive business strategies amid the rapid growth of the coffee industry.